Prevalence and antimicrobial susceptibility pattern of Escherichia coli in hospital acquired and community acquired patients related to urinary tract infection in India - Devanand Prakash and R.S. Saxena (Journal of Applied Pharmaceutical Science, 2013)
There is a dearth of information regarding to prevalence and antimicrobial susceptibility pattern of E. coli, a most common cause of nosocomial infections, in community and hospital acquired urinary tract infections. The antibiotic resistant pattern against E. coli varies when isolated from different sources. This study was carried out with an objective to isolate E. coli from male and female patients infected with hospital and community acquired UTI. The isolates were subjected to five different antibiotic categories comprising 18 antibiotics. On the basis of antibiotic resistance profiling MAR index was calculated. Prevalence of UTI was found 69.17% which was high in hospital (56.63%) than community settings (43.37%). Females were found more susceptible to UTI than males in both settings. Prevalence of E. coli was found 61.45% among all isolates. Carbepenems showed highest sensitivity against E. coli isolated from UTI patients. The highest MAR indices were 0.8 (3.57%) and 0.7 (8.69%) of E. coli isolated in hospital and community settings. The present study suggests that females are highly susceptible to UTI in both community and hospital settings as well as the occurrence of E. coli were also found high in female patients. E. coli showed resistance against commonly prescribed antibiotics.
Keywords: Escherichia coli, anti-micorbilas